New Media, Learning Outcomes, and Social Development of Children: A Case Study of Digital Technology Use in Nigeria - Nwoji, Queen; Gada, Bashiru Aliyu; Alqahtani, Zahra Mohmmed (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: The development of digital technology has brought about significant changes in the patterns of social interaction and learning outcomes of children, including in developing countries such as Nigeria. This study aims to investigate the impact of new media use on the social interaction and learning outcomes of children aged 8–12 years in Nigeria. Methodology: Using a mixed-method approach with a sequential explanatory design, data were collected from 220 respondents through questionnaires and in-depth interviews. Main Findings: The results showed that the majority of children use digital media, such as mobile phones and computers, not only for entertainment but also as a means of learning and social communication. A total of 59.6% of respondents had a good level of media use, while 64.6% demonstrated good social interaction, and 62.3% achieved positive learning outcomes. Regression analysis showed that new media use contributed 64.3% to the variation in children's social interaction and learning outcomes. This study confirms that with proper supervision and direction, digital media can be an effective tool to support children's social and academic development. Novelty/Originality of this study: These findings have important implications for education policy and the active role of parents and teachers in assisting children's use of digital media.